2016
DOI: 10.1002/adma.201600133
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Powered Electrochemistry for the Oxidation of Organic Molecules by a Cross‐Linked Triboelectric Nanogenerator

Abstract: A cross-linked triboelectric nanogenerator with high performance is designed for the first time, which harvests vibrational energy to self-power the electrochemical oxidation of organic molecules. This system lays the groundwork for applications to an environmentally friendly production of important organic molecules and the waste treatment of organic pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The organic pollutants containing benzene rings are generally residual in the environment and harmful to public health. Different technologies for treating water pollutants have been proposed, such as coagulation, adsorption, hydrolysis, , photocatalysis, and electrochemistry, as well as biodegradation. Among which, adsorption is selected as a much potential process because of the low cost, easy operation, outstanding designability, and high efficiency. …”
Section: Introductionmentioning
confidence: 99%
“…The organic pollutants containing benzene rings are generally residual in the environment and harmful to public health. Different technologies for treating water pollutants have been proposed, such as coagulation, adsorption, hydrolysis, , photocatalysis, and electrochemistry, as well as biodegradation. Among which, adsorption is selected as a much potential process because of the low cost, easy operation, outstanding designability, and high efficiency. …”
Section: Introductionmentioning
confidence: 99%
“…The C 1s XPS spectrum of SAC‐4 is shown as Figure b and the C 1s peak is dominated by a C–C bond (diamond and graphite type) at 284.7 eV. And C=N (285.4 eV), C=O (286.2 eV), C−N (287.1 eV) and O‐C=O (288.1 eV) can also be detected from the XPS spectrum . The N originates from the proteins in SCR and the N 1s XPS spectrum of SAC‐4 is shown as Figure c.…”
Section: Resultsmentioning
confidence: 97%
“…Besides the abovementioned works, some other SPESs such as SP electrochemical oxidation system and SP electrodeposition system were also developed to electrochemical synthesis [ 83 86 ]. Zheng et al reported an SP electrochemical oxidation system on the basis of designed cross-linked TENG for synthesizing polyaniline [ 85 ]. As for the cross-linked TENG, the high capability of 69.9 μ A and 845.6 V was achieved.…”
Section: Applications Of Self-powered Electrochemical Systemmentioning
confidence: 99%